Uma proposta de ensino para o estudo de calor e temperatura no 5º ano do ensino fundamental - Silva, Alessandra da (2018)
Through a didactic sequence it is possible to work physics concepts in the initial grades of elementary school, articulating key concepts and developing activities that allow the student to reflect on these concepts, making learning meaningful. The words Heat and Temperature are used daily to express thermal sensations, but one does not seek to understand the intrinsic meanings attached to them, and when merely exposed to the student they may not have real meaning, but with problem situations, ludic and experimental activities it is possible to transpose the so that the student interacts with what he already knows and internalizes this new knowledge by bringing to him the physical meanings as well as the interpretation of the associated phenomena, such as the definition of Heat, Temperature and Thermal Equilibrium. The application of the educational product was carried out in a group of twenty students of the fifth year of elementary school and proved effective in its objective which was the understanding of the concepts related to Heat and Temperature.